Lung microdialysis and in vivo PK/PD integration of cefquinome against Actinobacillus pleuropneumoniae in a porcine experimental lung infection model - Chen, Yuqin; Li, Min; Su, Dehai; Xiong, Shiyu; Feng, Youshu; Deng, Qin; Ding, Huanzhong (Frontiers in Veterinary Science, 2024)
This study aim to explore the the application of microdialysis in pharmacokinetic (PK) and pharmacodynamic (PD) integration of cefquinome against Actinobacillus pleuropneumoniae in a porcine experimental lung infection model. The model was established via intratracheal inoculation where average bacterial counts (CFU) in the lungs of infected pigs reached 6.57 log10 CFU/g after 3 h. The PK profiles of unbound cefquinome in lung dialysates were determined following intramuscular injection of single doses of 0.125, 0.25, 0.5, 1, 2, and 4 mg/kg. Lung dialysate samples were collected using microdialysis at a flow rate of 1.5 µL/min until 24 h. The PD studies were conducted over 24 h based on 10 intermittent dosing regimens and total daily doses ranged from 0.25 to 4 mg/kg and dosage intervals included 12 and 24 h. The lung tissue was collected after 24 h of treatment and homogenized for bacterial counts. The relationships between PK/PD parameters derived from lung dialysates and drug efficacy were analyzed using an inhibitory sigmoid Emax model. The percentage of time the free drug concentration exceeded the minimum inhibitory concentration (%fT>MIC) was the PK/PD index best describing the antimicrobial activity (R 2 = 0.96) in the porcine experimental infection model. The %fT>MIC values required to achieve net bacterial stasis, 1, 2 and 3 log10 CFU/g reductions in the lung were 22.45, 28.86, 37.62 and 56.46%, respectively. Cefquinome exhibited time-dependent characteristics against A. pleuropneumoniae in vivo. These results provide valuable insights into the application of microdialysis in PK/PD integration model studies and optima regimen of cefquinome for the treatment of porcine respiratory diseases caused by A. pleuropneumoniae.